Bone microstructure and atomic periodic disharmonization in osteoporosis - Zairin Noor; Mohammad Hidayat; Agus Hadian Rahim; Sutiman B. Sumitro (Universa Medicina, 2012)
BackgroundBoth cortical and cancellous bone display a complex, porous microstructure whose properties depend on the macrostructure of bone as well as age and health of the individual. The aim of this study was to compare the microstructure and characteristics of mineral atoms in osteoporotic and normal bone. MethodsA prospective laboratory experimental study was conducted from August to December 2010 at several hospitals in Banjarmasin. Twenty patients with osteoporosis and twenty six normal patients were involved in this study. Bone obtained from surgery was analyzed for microstructure by scanning electron microscopy (SEM), while mapping of mineral atoms was performed by means of SEM-Energy dispersive X-ray spectroscopy (SEM-EDAX) at the Brawijaya University, Malang.     ResultsThe osteoporotic subjects with mean age of 64.65 ± 16.41 years were older than the normal bone subjects with mean age of 39.38 ± 17.16 years. The body mass index was similar in both groups of subjects. From SEM-EDAX results, three patterns of mineral atoms were apparent in osteoporotic and normal bone. In osteoporotic bone, these patterns were indicative of a disordered substitution or incorporation process. SEM results showed degeneration of microarchitecture (resorption cavities, perforations, and prominent granules) in osteoporotic but not in normal bone. There was a significant difference in microstructure between osteoporotic and normal bone, which was caused by differences in atomic properties.    ConclusionsMicrostructural abnormalities of bone and disharmonization of mineral atoms in the periodic system were found in osteoporosis.